Analisis Nilai Moral dalam Naskah Drama Becik Nitik Ala Pilara Karya M. Ahmad Jalidu - Nazhiifah, Rifda Ummu; Saddhono, Kundharu; Said, Dewi Pangestu (Universitas Sebelas Maret, 2023)
The spread of moral issues in the community such as the use of narcotics and illegal drugs, pornography, brawls, rape, and so on are social issues of concern and have not been resolved. Drama script is one of the literary works that can be used as a tool to instill morals in the community in an effort to solve the problems that occur. This study aims to describe the representation of moral values in the drama script